Meta-Analysis Effects of Diabetes Mellitus on Mortality in Patients with Chronic Heart Failure - Windya Kartika Paramita; Yeocelin Mega Pratiwi (Masters Program in Public Health, 2022)
Background: Patients with diabetes mellitus have a higher risk of developing heart failure. Heart failure patients with diabetes mellitus will experience further health problems that are worse than heart failure patients without diabetes mellitus. This study was aimed to analyze the effect of diabetes on mortality in heart failure patients using a meta-analysis. Subjects and Method: This was a meta-analysis study using PRISMA flowchart guidelines. The PICO model used was Population= patients with chronic heart failure. Intervention= with diabetes mellitus. Comparison= not with diabetes mellitus. Outcome= mortality. The article search process was carried out between 2012 and 2021 using online databases from PubMed, Science Direct and Google Scholar. The keywords used in the article search were “Chronic Heart Failure” AND “Diabetes” AND “Mortality”. The inclusion criteria used in this study were full-text articles using a cohort study design, the research subjects were chronic heart failure patients, the study outcome was mortality, multivariate analysis with adjusted Hazard Ratio (aHR). The analysis was carried out using RevMan 5.3 software. Results: A total of 9 articles reviewed in the meta-analysis showed that diabetes mellitus increased the risk of mortality in patients with chronic heart failure 1.24 times compared with patients without diabetes mellitus (aHR= 1.24; 95%CI= 1.15 to 1.34; p< 0.001). Conclusion: Diabetes mellitus increases mortality in patients with chronic heart failure. Keywords: chronic heart failure, diabetes mellitus, mortality Correspondence: Yeocelin Mega Pratiwi. Faculty of Pharmacy, Universitas Gadjah Mada. Jl. Sekip Utara, Senolowo, Sinduadi, Sleman, Daerah Istimewa Yogyakarta 55281. Email: yeocelinmega@gmail.com. Mobile: +6282137652605.